KEBUTUHAN IKAN BAHAN BAKU INDUSTRI PINDANG DI PELABUHAN PERIKANAN PANTAI TASIK AGUNG REMBANG - Lubis, Ernani; Pane, Anwar Bey; Fatoni, Khoerul (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2019)
Fishing port plays a vital role in providing fish raw materials (IBB) required for fish processing industries (IPI). The planning and development of IPI at Tasik Agung Rembang Coastal Fishing Port (PPP) rely on information regarding IBB supplies, however little data is available to support the decision. The purpose of this study was to investigate the origin of the IBB in fulfilling IPI demand for Pindang production and assess the IBB actual supplies (type, number, quality). A survey on the availability of IBB was conducted by involving various stakeholders including port officers, fishers, and IPI related entrepreneurs. Data collection consisted of both demand and supplies of IBB, which incorporate types, volume, and quality of fish. The results showed that the total demand for IBB was 824.8 ton/month and consisted of 9 species. However, the existing supplies of IBB only cover 59.5% of it.Keywords: raw materials, pindang, Tasik Agung fishing port